PENGEMBANGAN MEDIA GOOGLE SITES DENGAN AR DAN PJBL: SOLUSI INOVATIF PEMBELAJARAN BANGUN RUANG DI ERA DIGITAL - Andriyani, Dewi; Sumartiningsih, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is one of the important disciplines in life because it can improve critical thinking skills to solve problems in life. This study aims to see the feasibility of developing Google Sites-based learning media integrated with Augmented Reality (AR) with the Project-Based Learning (PjBL) model to improve students' understanding of mathematical concepts of spatial shapes in Elementary School (SD). The method used in this study is qualitative with literature study techniques from various previous studies collected to show the effectiveness of using Google sites, AR, and PjBL in the context of education. The results of this study are that Google sites integrated with Augmented Reality can be utilized in the development of innovative learning media to improve students' understanding of spatial shapes.